The influence of cultural diversity on the effectiveness of Virtual Software Development Teams - Loskutova, Tetyana (My University, 2014)
A Virtual Software Development Team (VSDT) is a group team of Information Technology (IT) professionals working together to produce a software product and collaborating remotely with the use of information communication technology. In a VSDT, face-to-face contact is seldom required in order for these teams to fulfil their tasks. VSDTs in the software development business offer advantages compared to co-located teams which include the availability of a global talent pool, lower costs and a global presence. However, many aspects of managing these teams are still undiscovered and under-researched. Among them is the influence of cultural diversity on the work, productivity and sustainability of a VSDT. The purpose of this research was to define the main factors of the influence of cultural diversity on the effectiveness of a VSDT. The research was undertaken from an interpretive perspective. In agreement with this paradigm, the effectiveness factors were limited to the internal effectiveness of a team as perceived by its members. In order to define the factors of cultural diversity, existing theories of cultural diversity in a co-located workplace were used. I have conducted interviews with software developers, support professionals and their managers to probe the relevance of the existing theories in a virtual software development environment and to find other possible factors. In this research, a specific ’internet nerd’ culture was discovered which exists among the members of the virtual (internet) community. The members of this culture comfortably accept virtual work and share a lot of common context. The findings show the importance of frequent communication, emotional sharing and occasional face-to-face contact in bonding the team, building trust and understanding. From the team management perspective, there is evidence that agile methodologies can be used successfully in the virtual environment. The results of this research are beneficial for businesses looking to implement VSDTs, and can be used as a basis for the development of a theory of cultural diversity in a virtual environment.
Keywords: Software development; Teams; Cultural diversity; Internet community